Need for gender affirming clinics-a case report on gender dysphoria in India - Sood, Kanuja; Pal, Ved; Chamola, Sunil K.; Pathak, Vineet K. (International Journal Of Community Medicine And Public Health, 2023)
Evidence suggests that individuals with gender dysphoria/gender incongruence often experience a disproportionately high burden of disease, including in the domains of mental, sexual and reproductive health. Very few of the Lesbian, gay, bisexual, transgender, queer or questioning (LGBTQ) population seek medical or surgical treatments, others do not speak up for their condition because of the societal taboo and suffer from illnesses which fully impact the potential and well-being of the individual. We present a case of a 24-year old boy who never got treated for gender dysphoria and was ignored by the family, was made fun of by the society and ended up having Paranoid disorder secondary to gender dysphoria. This clearly indicates the need specialist health care professionals who can identify the individual for proper treatment and connect him to support groups, who can guide and educate the family and the society on the need to accept the individual in a way in which he wants to be accepted.